2020
DOI: 10.1093/mnras/staa3439
|View full text |Cite
|
Sign up to set email alerts
|

Environmental processing of galaxies in H i-rich groups

Abstract: We present and explore the resolved atomic hydrogen (H i) content of 13 H i-rich and late-type dominated groups denoted ‘Choirs’. We quantify the H i content of the Choir galaxies with respect to the median of the H i-mass fraction (f$_{\rm {{\small H\,{I}}}}$) of their grandparent Hipass sample. We find that the H i mass fraction of the Choir galaxies is dispersed around the Hipass median in the range -1.4≤Δf$_{\rm {{\small H\,{I}}}}\rm {[dex]}\le$0.7, from H i-excess to H i-deficient galaxy regime. The H i-e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 116 publications
1
1
0
Order By: Relevance
“…The HI envelopes of HI-deficient galaxies in filaments have likely been stripped, possibly via tidal interactions or ram pressure. For HI, our proposed scenario is in agreement with the findings of Džudžar et al (2021), who investigated environmental processing in late-type-dominated groups using high-resolution HI observations. These latter authors further discussed the possibility that groups with the highest levels of processing are transitioning towards Hickson compact or fossil groups, which are environments similar to those associated with the isolated ellipticals in our AMIGA comparison sample.…”
Section: Discussionsupporting
confidence: 89%
“…The HI envelopes of HI-deficient galaxies in filaments have likely been stripped, possibly via tidal interactions or ram pressure. For HI, our proposed scenario is in agreement with the findings of Džudžar et al (2021), who investigated environmental processing in late-type-dominated groups using high-resolution HI observations. These latter authors further discussed the possibility that groups with the highest levels of processing are transitioning towards Hickson compact or fossil groups, which are environments similar to those associated with the isolated ellipticals in our AMIGA comparison sample.…”
Section: Discussionsupporting
confidence: 89%
“…As an example, Fabello et al (2012) found evidence that RP strips atomic gas of galaxies in haloes more massive than 10 13 M , whereas this should not be expected in lower mass haloes (Taranu & et al 2014). In addition, Džudžar et al (2021) suggest that tidal interactions are the primary cause of the H i deficiency in group galaxies, while Oh et al (2018) show evidence that mergers prior to infall can induce morphological transformation in recently accreted cluster galaxies. By means of the Yosei Zoom-in Cluster Simulations (YZiCS), which consist in the hydrodynamical simulations of 16 galaxy clusters that span masses of 5×10 13 < M 200 /M < 10 15 , Jung et al (2018) study the excess of gas-poor galaxies in cluster environments.…”
mentioning
confidence: 99%